PEDAGOGICAL TECHNOLOGY OF COGNITIVE DEVELOPMENT SKILL - A STRONG BASIS FOR INDEPENDENT WORK OF STUDENTS WITH INFORMATION IN THE PROCESS OF ITS ASSIGNMENT - Yu.V. Reva (Academy of Cognitive and Natural Sciences, 2008)
The given artikle deals with pedagogical technology of cognitive skills development as the good basis for students self work.